Adjustment by size effect on the cost of equity: Pending practice in capital budget in Colombia - Reina Gutiérrez, Walther; Moscoso Escobar, Jenny; Montoya González, Carolina (Cuadernos de Administración, 2020)
This research identifies and analyzes the implications of capital budgeting techniques implemented by large, medium and small companies, related to the use and calculation of the discount rate - emphasizing in the cost of equity, adjusting it with a size premium and the calculation method of the latter- differentiating between the procedure of family and non-family businesses and the types of projects. Additionally, the same procedure is used for the viability indicators of the projects given their relevance in capital budget. For this, a descriptive analysis accompanied by contingency tables is made to a group of 182 Colombian companies. The results show that (i) only 14% of SMEs that evaluate their projects (93) adjust the discount rate with a size premium, (ii) procedures to define capital budget are more informal in family companies, (iii) expansion and replacement projects are more evaluated by family businesses, while mergers and acquisitions are more evaluated by non-family businesses, and (iv) there is little transfer of knowledge from the academy to the company.